Laser-induced graphene Janus membrane for electrothermal membrane distillation - Tan, Yong Zen (2022)
To improve the energy efficiency of membrane distillation (MD), localized heating of the feed-membrane interface is advantageous relative to heating of the bulk feed. This motivated the current study, which targeted at developing a simple two-step way of fabricating Laser-Induced Graphene (LIG) Janus membrane for electrothermal membrane distillation. Specifically, the Janus membrane had an electrically conductive graphene side and a polydimethylsiloxane (PDMS) coated polyethersulfone (PES) side. The PES membrane was first coated with PDMS in limonene (a green solvent) and the active layer exposed to low-powered laser. Joule heating was carried out on the LIG surface by connecting two electrodes to the opposite ends of the LIG surface and providing power with an alternating current power supply at regular household frequency. This Janus membrane can be heated on the LIG surface while insulated from heat loss on the PDMS-coated PES surface, resulting in a marked improvement in the MD performance. Relative to pre-heated feed at the same power input, Joule heating of the Janus membranes gave a flux increase of up to 119.5%, specific heating energy decrease of up to 53.9% and single-pass heat utilization efficiency increase of up to 119.5%, while maintaining excellent material stability.